Vibration analysis using the theory of exponential shear deformation for laminated plates - Khaled Bendahane; Mohammed Sehoul; Otbi Bouguenina; Abdelkrim Benahmed (The Journal of Engineering and Exact Sciences)
In this research, the free vibration response of laminated composite plates is studied using a refined exponential shear strain theory. The most interesting feature of this theory is that it allows exponential distributions of transverse shear strains, and verifies zero-shear boundary conditions on the plate surfaces without the use of shear correction factors. Some stiffness constants are written as a series. The number of independent unknowns in the present theory is four, compared with five in other shear deformation theories. The equations of motion are obtained from Hamilton's principle and Navier's method is used to determine the exact solution for antisymmetric cross-laminated plates. The numerical results found in the present analysis for free vibration are presented and compared with those available in the literature. The proposed theory is not only accurate, but also effective in predicting the fundamental frequencies of laminated composite plates.